Traces of memory: an exploration of print, fiber, and narrative - Method, Sara (2020)
Traces of Memory is a body of work focused on the role of memory, personal archives, and place. Memories exist at the boundary of reality and fiction. All the works of art in this exhibition are related to my experiences in my hometown of Bassett, VA – both in my childhood impressions of the place, and the incongruities of revisiting the town as an adult. In my creative research and process, I am seeking to use the language of prints and fibers to indicate the layering of impressions and loss of information when moving from physical experience of a place to the memory of place, and abstract impression of memory to the final impression of the traces of memory. The works of art discussed in this paper all attempt to capture a moment in time that is not concrete, and the imagery has the appearance of disappearing or dissolving. In my art practice, I utilize a naturalist’s approach of observing and recording in the field to explore interactions in our environments through fibers, sewing and cutting, drawing and prints, and writing narratives. The pathways of research, exploration, and creativity shift in this project as thoughts and memories refuse to stay fully within their vessel during the process of creating the work. Through the lens of creative research and art practice, I will mine my own personal archive of memories to trace paths of connection as I attempt to discover what impressions are left by childhood experiences and a sense of community.